2022
DOI: 10.1039/d2cp03202c
|View full text |Cite
|
Sign up to set email alerts
|

Pulse length dependence of photoelectron circular dichroism

Abstract: We investigated photoelectron circular dichroism (PECD) using pulses with various durations. From the experiment with fenchone, we found constancy of the PECD over a wide range of pulse durations and estimated lifetimes of internal conversions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…These include microwave three wave mixing, 1–4 Coulomb explosion imaging, 5–7 along with photoion circular dichroism (PICD) 8–17 and photoelectron circular dichroism (PECD). 12,13,18–62…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include microwave three wave mixing, 1–4 Coulomb explosion imaging, 5–7 along with photoion circular dichroism (PICD) 8–17 and photoelectron circular dichroism (PECD). 12,13,18–62…”
Section: Introductionmentioning
confidence: 99%
“…This sensitivity has been used to probe the ultrafast excited state dynamics in fenchone in separate experiments using a two-colour pumpprobe scheme 34,35 and by exploring how PECD evolves as a function of pulse length. 52 Another experiment using a cooled molecular beam and a tuneable, narrowband nanosecond laser found that the PECD was not strongly dependent on the intermediate vibrational state populated, possibly due to the Rydberg nature of the resonance. 44 Another important consequence of the population of an intermediate state is that the anisotropy of the excitation results in preferential ionization of molecules with certain orientations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, fenchone has become established as the prototypical molecule for the introduction and study of laser-driven PECD phenomena, in particular those using resonance enhanced multiphoton ionization (REMPI-PECD). 13–24 Just as in single photon PECD phenomena, photoelectron angular distributions that are forward/backward asymmetric with respect to the propagation direction of a circularly polarized laser beam are observed. These arise from pure electric dipole interaction of the ionizing photon with the molecular target, resulting in very strong chiral asymmetry factors that may range up to several tens per cent.…”
mentioning
confidence: 97%
“…A number of REMPI-PECD studies using fenchone have explicitly sought insight into the role played by these Rydberg intermediates, primarily by comparing excitation through different bands of the Rydberg spectrum. [15][16][17] Comparisons with different laser pulse durations further reveal that excitation through the 3p states can be subject to internal conversion to a 3s Rydberg state preceding the ionization step, [15][16][17][18] while the implied rapid non-adiabatic dynamics results in different ion vibrational distributions with a corresponding influence upon the PECD asymmetry being observed. 17 Direct time-resolved REMPI-PECD experiments with a delayed pump-probe have demonstrated additional ultrafast relaxation processes and rotational dephasing of the intermediate alignment that may occur prior to ionization of the intermediate.…”
mentioning
confidence: 99%